Lateralization for speech predicts therapeutic response to cognitive behavioral therapy for depression. Issue 3 (30th August 2015) - Kishon, Ronit; Abraham, Karen; Alschuler, Daniel M.; Keilp, John G.; Stewart, Jonathan W.; McGrath, Patrick J.; Bruder, Gerard E.
Abstract: A prior study (Bruder, G.E., Stewart, J.W., Mercier, M.A., Agosti, V., Leite, P., Donovan, S., Quitkin, F.M., 1997. Outcome of cognitive-behavioral therapy for depression: relation of hemispheric dominance for verbal processing. Journal of Abnormal Psychology 106, 138–144.) found left hemisphere advantage for verbal dichotic listening was predictive of clinical response to cognitive behavioral therapy (CBT) for depression. This study aimed to confirm this finding and to examine the value of neuropsychological tests, which have shown promise for predicting antidepressant response. Twenty depressed patients who subsequently completed 14 weeks of CBT and 74 healthy adults were tested on a Dichotic Fused Words Test (DFWT). Patients were also tested on the National Adult Reading Test to estimate IQ, and word fluency, choice RT, and Stroop neuropsychological tests. Left hemisphere advantage on the DFWT was more than twice as large in CBT responders as in non-responders, and was associated with improvement in depression following treatment. There was no difference between responders and non-responders on neuropsychological tests. The results support the hypothesis that the ability of individuals with strong left hemisphere dominance to recruit frontal and temporal cortical regions involved in verbal dichotic listening predicts CBT response. The large effect size, sensitivity and specificity of DFWT predictions suggest the potential value of this brief and inexpensive test as an indicator of whether a patient will benefit from CBT for depression. Highlights: Replicated larger left hemisphere dominance for speech in CBT responders. Larger left hemisphere advantage associated with greater improvement following CBT. Neuropsychological tests or premorbid IQ did not predict response to CBT. Dichotic Fused Words Test predictions had high sensitivity and specificity.